Table of Contents - Board, Editorial (Law, State and Telecommunications Review, 2026)
This issue of the Law, State and Telecommunications Review brings together articles that examine some of the most pressing legal, regulatory, and institutional challenges emerging from contemporary digital transformation. The contributions address the digital transformation of public services and government bodies, the implementation of e-government in different regions, and the legal foundations of information security policy in a global society. The issue also includes studies on cybersecurity, cybercrime, cryptocrime, blockchain-based electronic payments, digital assets, cybersquatting, and the legal responses required to protect fair competition, financial security, and trust in digital environments. Additional articles explore the role of cyberattacks in political and economic stability, the regulation of digital surveillance and spyware, and the interaction between human rights and cybersecurity in modern international law. Finally, this volume addresses emerging regulatory frontiers in artificial intelligence, including the use of AI in law enforcement and the future-proof character of the EU AI Act, as well as the environmental and legal challenges associated with green telecommunications deployment. Taken together, the articles offer a broad comparative and interdisciplinary perspective on how law and regulation are adapting to digital infrastructures, data-driven societies, cybersecurity risks, and new forms of technological governance.